Neuroprotection against glutamate-induced excitotoxicity and induction of neurite outgrowth by T-006, a novel multifunctional derivative of tetramethylpyrazine in neuronal cell models. (October 2016) - Xu, Daping; Chen, Haiyun; Mak, Shinghung; Hu, Shengquan; Tsim, Karl W.K.; Hu, Yuanjia; Sun, Yewei; Zhang, Gaoxiao; Wang, Yuqiang; Zhang, Zaijun; Han, Yifan
Abstract: Alzheimer's disease is a progressive neurodegenerative disorder, characterized by irreversible impairment of memory and cognitive function. The exact causes of Alzheimer's disease still remain unclear and current single target drugs could only offer limited therapeutic effect to the patients. We have previously reported that T-006, a promising anti-Alzheimer's compound derived from Chinese medicinal component tetramethylpyrazine, might protect neurons through inhibiting the overproduction of intracellular reactive oxygen species (ROS) and reactive nitrogen species (RNS). In this study, we further investigated the neuroprotective effects, as well as the molecular pathways involved, of T-006 against glutamate-induced excitotoxicity in rat cerebellar granule neurons (CGNs). T-006 was also found to promote neuronal differentiation in both PC12 cells and primary cultured rat cortical neurons. The results showed that the pretreatment of T-006 (0.01–1 μM) might prevent glutamate-induced neuronal loss in a concentration-dependent manner. T-006 is found to inhibit the over-activation of NMDAR and ensued calcium overload caused by glutamate. The following activation of phosphorylated extracellular signal-regulated kinase (ERK) were also abolished. Moreover, T-006 concurrently prevented the suppression of phosphorylated protein kinase B (Akt) and glycogen synthase kinase 3β (GSK3β). T-006 was also found to promote neurite outgrowth in PC12 cells and primary cortical neurons. In our study, T-006 (0.1–3 μM) dose-dependently stimulated neurite outgrowth in PC12 cells and the efficacy was comparable to nerve growth factor (NGF). Moreover, co-treatment of T-006 and NGF revealed that T-006 could robustly potentiate the NGF-induced neuritogenesis. Further signal transduction studies indicated that T-006 rapidly up-regulated phosphorylation of ERK but did not activate tyrosine kinase receptor A (Trk A). These findings offer deeper understanding of the anti-neurodegenerative activity of T-006 and provide insight into its possible therapeutic potential for AD treatment in light of the multipotent nature of T-006. Highlights: Novel TMP derivative, T-006, prevents glutamate-induced cell death in rat CGNs 100 times more potently than memantine. The protection of T-006 is achieved by concurrent antagonizing NMDA receptor and regulating PI3K/AKT pathway. T-006 promotes neurite outgrowth in both PC12 cells and rat primary cortical neurons. T-006 is a multi-potent compound that exhibits activity in multiple models of Alzheimer's disease.